A Rare Anatomical Variation of the Termination of Right and Left Cephalic Veins - Raymond Saa-Eru Maalman; Yaw Otchere Donkor; Ali M. Ayamba; Jubilant Kwame Abledu (Case Reports in Vascular Medicine)
Clinically, the cephalic vein is preferred for haemodialysis in patients with chronic renal failure (CRF), to remove waste products from blood. The cut-down of cephalic vein in the deltopectoral groove is preferred when superior vena caval infusion is necessary. However, cephalic veins exhibit a wide array of developmental variations in terms of formation, course, and termination. In this report, we describe a case of an anomalous cephalic vein with a bifid course of terminations on both left and right upper limbs which has not been described by previous literature. During routine gross anatomy dissection of the neck, we observed a rare case of variation of the termination of the cephalic vein in both right and left upper limbs, of a male cadaver. Knowledge of the variations of cephalic vein is important not only for anatomists but also for surgeons and clinicians as the vein is frequently used for different surgical procedures and for obtaining peripheral venous access as well.